2023
DOI: 10.1038/s41598-023-28691-0
|View full text |Cite
|
Sign up to set email alerts
|

Truncated ring-A amaryllidaceae alkaloid modulates the host cell integrated stress response, exhibiting antiviral activity to HSV-1 and SARSCoV-2

Abstract: The total synthesis of four novel mono-methoxy and hydroxyl substituted ring-A dihydronarciclasine derivatives enabled identification of the 7-hydroxyl derivative as a potent and selective antiviral agent targeting SARSCoV-2 and HSV-1. The concentration of this small molecule that inhibited HSV-1 infection by 50% (IC50), determined by using induced pluripotent stem cells (iPCS)-derived brain organ organoids generated from two iPCS lines, was estimated to be 0.504 µM and 0.209 µM. No significant reduction in or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Sprekelia formosissima was used [6,10-3 H 2 ; 12-14 C] noroxomaritidine for labelling, which resulted in incorporations of 0.03% into ismine, 2% into haemanthamine, and 0.8% into haemanthidine. Ismine showed no 14 C activity. The radioactive ismine's labelling pattern was indirectly determined by its conversion into phenanthidone, which retained approximately 25% of the tritium activity.…”
Section: Reviewmentioning
confidence: 91%
See 4 more Smart Citations
“…Sprekelia formosissima was used [6,10-3 H 2 ; 12-14 C] noroxomaritidine for labelling, which resulted in incorporations of 0.03% into ismine, 2% into haemanthamine, and 0.8% into haemanthidine. Ismine showed no 14 C activity. The radioactive ismine's labelling pattern was indirectly determined by its conversion into phenanthidone, which retained approximately 25% of the tritium activity.…”
Section: Reviewmentioning
confidence: 91%
“…125,130 7-Hydroxyl derivative trans-dihydrolycoricidine and dihydronarciclasine analog lacking the methylenedioxy group, with a C7-OH on ring-A, and a fully functionalized ring-C (no double bond but 3 hydroxyl in a similar orientation as lycoricidine) efficiently targeted HSV replication, whereas other modications of dihydronarciclasine analog, including hydroxylation or O-methylation of C9, were not active. 13 As both derivatives affected the elF2 pathway involved in protein translation, 14 triggered autophagy and apoptosis-related signalling pathways involving ERK and Sirtuin-1, ring B and C stereocenters appear to be key to their activity. Previous studies by Gabrielsen and Jimenez et al showed that ring C hydroxyls were crucial for antiviral activity and that the C1-C10b double bond was associated with increased cytotoxicity, while C7 deoxy derivatives led to lower cytotoxic properties.…”
Section: Natural Product Reports Reviewmentioning
confidence: 99%
See 3 more Smart Citations